Determination of Calcium in Wort by Atomic Absorption Spectrophotometry: Submitted on behalf of the Analysis Committee of the European Brewery Convention - Hagen, W. (BrewingScience, 2002)
The Analysis Committee of the European Brewery Convention (EBC) decided to test the determination of calcium in wort according to Analytica-EBC method 9.19 Calcium in Beer by Atomic Absorption Spectrophotometry (1). In spring 2001 an inter-laboratory trial was organised using four samples of wort with different calcium levels in the range of 20 – 150 mg/l. Ten members of the EBC Analysis Committee and one laboratory from Weihenstephan participated in this collaborative trial